Economic status and anxiety level in third trimester of pregnant women in facing normal labor: A cross-sectional study - Sukmanawati, Dera; Yuliani, Eris (Journal of Midwifery, 2024)
The process of pregnancy and childbirth is a natural thing for a woman, but before the delivery process, a mother often feels anxiety. One of the factors that influence anxiety during pregnancy is economic status. This study aims to analyze the relationship between economic status and the level of anxiety of pregnant women in the third trimester in the face of normal delivery in the Work Area of Sodonghilir Health Center, Tasikmalaya Regency in 2022. This type of research is quantitative with observational analytic methods and a cross-sectional approach. The sample in this study was 37 third-trimester pregnant women, obtained by accidental sampling technique. The research instrument used a questionnaire. Bivariate analysis using spearman rank statistical test. The results of the univariate analysis showed that most of the economic status of pregnant women in the third trimester, including the upper class, was 64.9%. The anxiety level of pregnant women in the third trimester of pregnancy mostly experienced mild anxiety, namely 54.1%. the results of the bivariate test obtained a p-value 0,000 which mean there is a relationship between economic status and the level of anxiety of pregnant women in the third trimester of childbirth. It is recommended for the Sodonghilir Health Center improve health services, especially for pregnant women in the third trimester by providing information communication and education regarding childbirth preparation so that it can reduce anxiety in maternity mothers